Sistem Informasi Katalog Produk Berbasis Web Dengan Metode USER-CENTERED DESIGN - Haniyah, Husna; Samsudin, Samsudin (Jurnal Ilmiah Media Sisfo, 2025)
Many e-commerce systems focus on business, with various features but do not involve users, to the point of not necessarily in accordance with the needs of the user, in terms of usability, interface, and some features presented information, and some stories from the process used, due to several factors - these factors make users feel difficulty or frustration in using the application and become the cause of decreased user productivity. So the solution is to create an e-commerce application that is easy and simple to use according to user needs with the User-Center Design (UCD) method. What is offered Ease can attract more potential buyers. However, owners or mid-level corporate organizations such as PetZone currently rarely offer easy ways to shop or order services or do it online. Therefore, a web-based system is needed at PetZone that can facilitate owners or employees in sales, services, and marketing, as well as facilitate customers in buying and selling goods or services. From this problem, researchers wrote a Web-Based Sales and Service Ordering Information System so that it is expected to have a positive impact in facilitating the buying and selling process and can increase business competition to market various products and services. The UCD method implements with the aim of producing applications with high utility value, including convenience in use, management, effectiveness, and suitability of applications to user needs. This Web-based E-catalog Information System is to increase efficiency or provide convenience in displaying products in the form of a digital product catalog that has a modern, complete and concise appearance.